Service-learning code of ethics (Anker Pub. Co., 2005)
Divided into four parts, this book: Provides a synopsis of the theoretical context of moral decision-making; principles that are most relevant to ethical decision-making in service-learning; a proposed code of ethics for students, faculty, and administrators; and a model of ethical decision-making; Reviews current literature on formative and summative assessment in service-learning, and provides an overview of risk management; Includes an appendix of additional hypothetical dilemmas that consider several perspectives, followed by a set of questions to guide the reader through the model of ethical decision-making; Presents hypothetical ethical dilemmas for students, faculty, and administrators, followed by the application of a model of ethical decision-making to resolve the dilemmas